Niemann-Pick disease type C with kidney involvement - Aanand A. Patel; Anthony Sisk; Jonathan E. Zuckerman (Elsevier, 2021)
Niemann-Pick disease type C is a lysosomal storage disease characterized by defects in lipid trafficking, typically involving the liver, spleen, and central nervous system. Only rare reports of renal involvement of Niemann-Pick disease have been reported and to date have only been described in type A and B forms of the disease. We report for the first time the kidney biopsy findings in a 21-year-old woman with Niemann-Pick disease type C and nephrotic-range proteinuria. Light microscopy demonstrated foamy podocytes, vacuolated tubular epithelial cells and collections of foam cells in the interstitium. Focal segmental glomerulosclerosis as well as diffuse global glomerulosclerosis were present. Electron microscopy showed myelin-like inclusions in podocytes, endothelial cells, tubular and epithelial cells. The inclusions were similar to those found in Fabry's disease. This case illustrates Niemann-Pick disease as an important differential diagnosis for myeloid bodies. Additionally, this case highlights that glomerular involvement by Niemann Pick disease can result in nephrotic range proteinuria.